Food: Is a Crisis Looming - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1996)
This paper reviews the literature on the prospects of the world food supply-demand situation over the next decade and beyond. In particular, space is provided for the growth patterns and projections of food production, consumption, trade and world prices. This also includes analysis of possible constraints in increases of future food production. Implications of the projected food demand-supply balance are also discussed.
Keywords: 330; food sector; food price stability